Putusan Mahkamah Konstitusi Terkait Usia Calon Presiden dan Calon Wakil Presiden - Christine S.T Kansil; Destiana Vani Candra (Universitas Ekasakti, 2024)
The Constitutional Court is an institution of judicial power based on the constitution and has a judicial function to uphold law and justice. Based on the 1945 Constitution of the Republic of Indonesia, state power is divided into three parts, namely legislative, executive and judicial. The authority of the Constitutional Court is regulated in Article 24C of the 1945 Constitution, namely that the Constitutional Court functions to adjudicate at the first and last level and its decisions are final. Constitutional Court decisions in reviewing laws relate to formal and material aspects, so consideration is required by the judge as a basis for a decision. This article was written to review the authority of the Constitutional Court in judicial review and regarding the inconsistency of the Constitutional Court in decision Number 90/PUU-XXI/2023 concerning the age requirements for presidential and vice-presidential candidates.